Ultrasonic optic nerve diameter measurement among pregnant women in a specialist hospital, Port Harcourt, Rivers State, Nigeria - Ugboma, Enighe W.; Akagbue, Vivian Ndidi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Elevated intracranial pressure (ICP) during pregnancy can pose significant health risks. Ultrasonic measurement of optic nerve diameter offers a safe, non-invasive method for assessing ICP. Establishing normative data for optic nerve diameter in pregnant women is essential for future evaluations. This study aims to document the optic nerve diameter in healthy pregnant women and examine associations with maternal characteristics, including age, parity, and body mass index (BMI). Methods: An eight-month prospective cross-sectional study involving 559 healthy pregnant women attending the Radiology department of a specialist hospital in Port Harcourt, Nigeria was conducted. Demographic and anthropometric data were collected. Optical nerve diameters were measured via ultrasound at 3 mm behind the globe, and statistical analyses, including Pearson correlation coefficients, were performed to assess relationships with maternal factors. Results: The mean age of participants was 29.95 years (SD±6.34). The mean right and left optic nerve diameters were 0.57 cm (SD±0.082) and 0.58 cm (SD±0.08). Significant negative correlations were found between optic nerve diameter, age (left r =-0.158, p=0.001), and parity (right: r=-0.100, p=0.007). No significant associations were observed with weight, height, or BMI. Conclusion: This study establishes baseline optic nerve diameter measurements for healthy pregnant women, with significant correlations observed with age and parity. These findings contribute to understanding maternal health and provide a foundation for further research on optic nerve diameter as an indicator of ICP in pregnancy. Multi-Centre studies are recommended to validate and expand upon these results.